Adaptive immune stimuli altered the cargo proteins of exosomes released by supraneural myeloid body cells in Lampetra japonica. (July 2019) - Wang, Hao; Cheng, Xianda; Li, Mengjiao; Li, Wenna; Zhu, Ting; Li, Qingwei
Highlights: Exosomes released by the supraneural myeloid body cells in lamprey are purified. Exosomes are evolutionarily conserved between lamprey and other higher species. Immunization of lamprey with lipopolysaccharide can alter the exosomal proteins. Quiescent and activated exosomes may have different immunomodulatory functions. Abstract: As one of the representatives of jawless vertebrates, lamprey is an important animal model for research on the evolution of adaptive immune system. Although it is widely accepted that the key characteristic of the immune response in jawed vertebrates is the functional cooperation between different immune effector cell lineages, whether immune cells of lamprey can communicate with each other is still unclear. Recently, mounting evidence has revealed the emerging role of exosomes in mediating intercellular communication. In this study, by means of ultrafiltration followed by size exclusion chromatography, exosomes are purified from conditioned growth medium of the primary supraneural myeloid body cells (SMB cells) in LPS-immunized and control Lampetra japonica (Japanese lamprey). The proteomic profiling and qualitative comparison are performed between protein components enriched in exosomes released by SMB cells under quiescent and activated conditions. Our results demonstrate that SMB cells can release exosomes with well-defined characteristics comparable to their mammalian counterparts on their size, morphology and protein markers, which supports exosomes are evolutionarily conserved between lamprey and other higher vertebrate species. In terms of comparison with exosomes released by quiescent SMB cells, activated SMB cell-derived exosomes contain more and significantly different protein components. The unique exosomal protein 'fingerprint' might reflect that exosomes from the SMB cells with different states of activation have distinguishing functional roles as well as targeting properties. Further bioinformatic analysis suggests that compared to quiescent exosomes, activated SMB cell-derived exosomes mainly participate in distinctive biological processes including activation of cellular component biogenesis and regulation of cell proliferation. Moreover, activated exosomes may function through the specific signaling pathways associated with the regulation of cell mitosis and immune response. Our results give valuable clues about the immunomodulatory functions of SMB cell-derived exosomes and provide the foundation for further investigation in the regulation mechanism of the adaptive immune response in lamprey.